High resolution geomorphological classification of benthic structure on the Western Pacific Seamount - Fan, Miao; Shi, Suixiang; Ma, Yong; Wang, Hu; Zhai, Jingsheng; Zhang, Xuefeng; Ning, Pengfei (Frontiers in Marine Science, 2022)
The benthic structure of seamounts is critical to understand the ecological environment and to assess the influence of resources exploitation. However, the characteristics of benthic structure for seamount, especially for guyot, a kind of flat-topped seamount particularly developed in Western Pacific Ocean (WPO), is still far from being clearly understood. For the first time, we carry out the detailed hydro-acoustic mapping in conjunction with surficial sediment sampling, and underwater video recording to investigate the geomorphical and biological characteristics of Pallada Guyot in the WPO. Among which, we utilized Benthic Terrain Modeler (BTM) as an initial step to describe the detailed benthic structures, then classify the textural seabed according to backscatter images and sediment samples. Moreover, we further discuss the relationship between geomorphology and the occurrence of the benthic megafauna from video images. Results reveal that 13 classes of benthic structure zones are differentiated. The dominate zones are flat abyssal plains, where the number and size of megafauna is smaller than that on the flank and flat-topped areas. The second most notable features are the flat tops, where sea cucumbers, starfish, fish and shrimps have higher biomass and diversity. In the flank region, characterizing as complex and extensive current-scoured ridges and depressions, sponges and corals distribute on high relief bedrocks. We also find some unique features of the benthic structure of WPO seamount, for example, the maximum water depth where cold water corals developed is 2250 m, which is much deeper than that of 1500 m for seamounts in North Atlantic and Southern Hemisphere between 20°and 50°S. Moreover, the sponge grounds appear in a marked bathymetric belt (1,800 – 2,150 m), which is shallower than that on tropic seamount (2,500 – 3,000 m) in the Northeastern Atlantic. The findings of this paper may contribute to understanding the geomorphological drivers and biogeography of WPO seamounts, providing reference to identify priority areas for improved marine mineral planning in WPO areas.